Design and development of low cost bieceps tendonitis physiotherapy monitoring system using surface EMG electrodes for automated rehabilitation - Poo, Tarn Shi (School of Mechatronic Engineering, 2011)
This research attempts to design and develop a low cost EMG acquisition system for monitoring biceps tendonitis physiotheraphy.